2016
DOI: 10.1016/j.jstrokecerebrovasdis.2015.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Wake-up Stroke and Stroke within the Therapeutic Window for Thrombolysis Have Similar Clinical Severity, Imaging Characteristics, and Outcome

Abstract: Background: Wake-up stroke (WUS) represents 25% of all ischemic strokes. There is conflicting evidence concerning clinical severity, imaging characteristics, and outcome when WUS is compared with stroke of known time of onset. Our aim was to compare WUS patients with patients with ischemic stroke within the therapeutic window (STW) for thrombolysis. Methods: This is a retrospective hospitalbased study of all consecutive patients hospitalized for acute ischemic stroke during 2013. Patients with STW, WUS, and WU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
(20 reference statements)
2
7
0
Order By: Relevance
“…Further, our results suggest that there are no differences in baseline characteristics between WUS and KOS. These findings are in line with previous studies and underline the concept that patients with WUS are comparable candidates for reperfusion strategies . The frequency of IV tPA‐treated WUS was found to be 7.2%, which increased continuously over the whole study period.…”
Section: Discussionsupporting
confidence: 91%
“…Further, our results suggest that there are no differences in baseline characteristics between WUS and KOS. These findings are in line with previous studies and underline the concept that patients with WUS are comparable candidates for reperfusion strategies . The frequency of IV tPA‐treated WUS was found to be 7.2%, which increased continuously over the whole study period.…”
Section: Discussionsupporting
confidence: 91%
“…In another study, WUS patients were not at increased odds for unfavorable functionality or in-hospital mortality after adjustment for age, NIHSS score on admission, and IV-rtPA use [5]. In one study comparing patients imaged within 4.5 h after symptom onset in WUS patients, WUS patients had lower pc-ASPECTS scores comparable to our results [22]. Studies that compared WUS patients to patients with a known time to symptom onset of < 3 h showed no difference in ischemic changes on NCCT findings [9, 23].…”
Section: Discussionsupporting
confidence: 81%
“…In a previous study, no significant differences were shown in clinical features between patients with a WUS and patients with a known onset time of their stroke [5, 6, 9, 21, 22]. In another study, WUS patients were not at increased odds for unfavorable functionality or in-hospital mortality after adjustment for age, NIHSS score on admission, and IV-rtPA use [5].…”
Section: Discussionmentioning
confidence: 97%
“…31 Indeed, it was shown that clinical and imaging characteristics in WUS and stroke eligible for intravenous thrombolysis seem to be comparable, whereas DUS-as in our cohort-tends to have a worse prognosis. 13,32,33 We did not observe significant differences in baseline characteristics. Longer imaging-to-groin times in WUS and DUS can be explained by a higher percentage of MR imaging scans and might indicate a careful patient selection.…”
Section: Discussionmentioning
confidence: 51%